On the issue of mechanical activation of burnt moulding waste (Международный научный журнал «Инженер», 2026)
This article is devoted to the study of the processes of mechanical activation of burnt moulding waste (BMW) with the aim of using it as a highly active mineral additive in building materials. In the course of the work, the kinetics of BMW grinding and its dependence on technological parameters were studied. Experiments have shown that mechanical activation leads to a significant increase in the specific surface area of BSF and its amorphisation, which increases the reactivity of the material. The data obtained confirm that BSF, after mechanical activation, can serve as an effective component for improving the properties of cement composites.